Rule of law or rule of security: rethinking legal responses to organised crime amid hybrid threats - Melnychuk, Tetiana; Мельничук, Тетяна Володимирівна; Мельничук, Т. В. (Одеса : Фенікс, 2026)
These developments reflect the growing need for a new legal architecture capable of functioning in conditions of non-linear change and «unstable normality». They also address the need of a model of adaptive, hybrid threat-resilient legal system that relies on institutional flexibility and transparency, maintaining its democratic nature even under the pressure of exceptional circumstances.
Melnychuk T. Rule of law or rule of security: rethinking legal responses to organised crime amid hybrid threats. Соціально-політична та правова система України в цифрову епоху: сучасні виклики : матеріали Міжнар. наук.-практ. конф. (м. Одеса, 22 квіт. 2026 р.) : у 2-х т. / заг. ред. С. Ківалова ; НУ «Одес. юрид. академія». Одеса : Фенікс, 2026. Т. 1. С. 523-526. URL: https://doi.org/10.32837/11300.33229
Keywords: організована злочинність; гібридні загрози; протидія; верховенство права; секьюритизація; organised crime; hybrid threats; counteraction; rule of law; securitisation